Revisiting Interregional Wage Differentials: New Evidence from Spain with Matched Employer-Employee Data - Inés P. Murillo Huertas; Raul Ramos; Hipólito Simón (Institute of Labor Economics (IZA), 2017)
This study examines wage differences across Spain's regions along the entire wage distribution based on matched employer-employee microdata from 2006 to 2014. Unlike previous studies, we control for differences in regional purchasing power parities, which are very large in practice. Although many of the raw wage differences observed are explained by differences between regional productive structures and, to a lesser extent, in labour forces, noteworthy regional differences net of composition effects remain after controlling for a broad set of individual and firm characteristics. Unexplained wage differences are generally very similar throughout the wage distribution and are strongly persistent over time, despite significant changes in both economic cycle and labour regulations that occurred in Spain during the examined period. This evidence suggests the presence of common mechanisms in the generation of regional wage differentials that affect the whole labour force and that are strongly persistent over time, which is consistent with a key role of collective bargaining
Keywords: J31; J52; 330; interregional wage differentials; decomposition methods; matched employer-employee data; wage setting institutions